Биохимические механизмы кариеспрофилактического действия гексафторсиликатов = Biochemical mechanisms of the caries prophylaxis action of hexafluorosilicates - Lepsky, V. V.; Anisimov, V. Yu.; Lepsky, V. V. (Journal of Education, Health and Sport, 2015)
Lepsky V. V., Anisimov V. Yu., Lepsky V. V. Биохимические механизмы кариеспрофилактического действия гексафторсиликатов = Biochemical mechanisms of the caries prophylaxis action of hexafluorosilicates. Journal of Education, Health and Sport. 2015;5(11):289-299. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34024 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A289-299 https://pbn.nauka.gov.pl/works/670448 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015. УДК 616.31+612.084+546.161 Биохимические механизмы кариеспрофилактического действия гексафторсиликатов Biochemical mechanisms of the caries prophylaxis action of hexafluorosilicates В. В. Лепский1, В. Ю. Анисимов2, В. В. Лепский1 V. V. Lepsky1, V. Yu. Anisimov2, V. V. Lepsky1 1ГУ «Институт стоматологии НАМН Украины» (г. Одесса, Украина) 2Одесский национальный медицинский университет (Украина) 1SE«The Institute of Stomatology of the National acfdemie of medical science of Ukraine» (Odessa, Ukraine) 2Odessa National Medical University (Ukraine) Summary Aim: To determine the biochemical mechanisms of the anticariotic action of hexafluorosilicates and select the most active of them. Methods: In this work there were used 5 "onium" hexafluorosilicates (containing NH3, chlorhexidine, polyhexamethyleneguanidine, cetylpyridinium, pyridoxine) and sodium fluoride. Those were used in the form of gels and applied on teeth and gums in the dose containing 1.36 mg / kg of fluoride per day. The caries prophylaxiseffectiveness was evaluated by the number of dental caries in rats treated with the Stefan‘s cariogenic diet for 35 days. Alkaline (AlP) and acid (AcP) phosphatases‘ activities among with lysozyme activity were determined in the dental pulp. The index of mineralized pulp was calculated as the ratio AlP / AcP. Results: All tested hexafluorosilicates were more effective than sodium fluoride. The most efficient was cetylpyridinium hexafluorosilicate in the dose 15 mg / kg. The biochemical mechanism of the caries prophylaxis action of hexafluorosilicates is the activation of alkaline phosphatase AlP and pulp‘s lysozyme. Keywords: hexafluorosilicates, dental caries, pulp, phosphatase, lysozyme, oral gels. Резюме «Ониевые» гексафторсиликаты (ГФС) обладают более высокой кариеспрофилактической эффективностью по сравнению с фторидом натрия. Наиболее активным оказался цетилпиридиниевый гексафторсиликат в дозе 15 мг/кг при использовании в виде оральных аппликаций геля. Механизм действия ГФС состоит в активации щелочной фосфатазы и лизоцима пульпы зубов. Ключевые слова: гексафторсиликаты, кариес зубов, пульпа, фосфатаза, лизоцим, оральные гели.